Mindscapes and Landscapes: Learning to Adapt in Transnational Climate Adaptation Collaborative in Africa - Manteaw, Bob Offei (Consilience, 2020)
This paper foregrounds notions of learning and how they are framed in transnational adaptive capacity building processes. While supporting emerging adaptation governance mechanisms that recognize the boundlessness of climate change impacts, the paper draws attention to learning and the role it plays in such processes. Learning, for the most part, is framed as an event rather than a series of conscious, reflexive, adaptive and multi-layered processes. Such framing, the paper argues, is limiting and is based on flawed understandings of adaptation to climate change. Instead, learning should reflect the underlying complexity of both the climate change phenomenon and socio-ecological systems change processes. This paper argues that current conceptualization of climate change fails to present climate change as emerging, evolving and complex and, in the process, influences how learning in adaptation is perceived, framed and pursued.